Comparative Assessment of Trends of Social Anxiety and Social Avoidance during First and Second Wave of Covid-19 - Mirza Zeeshan Sikandar, Muhammad Abu Bakar, Haris Aleem, Aneeza Tufail, Aiman Fatima, Muhammad Umar Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Corona virus disease 2019 (COVID-19) was first reported in China and became the global pandemic. This pandemic has proven fatal for the world and lasts drastic effects on the whole world. To combat with this hilarious pandemic, the whole world has adopted the strategy of social distancing and precautionary measures. Aim: To compare trends of social anxiety and avoidance during covid wave 1 and covid wave 2. Methodology: A cross-sectional study was conducted at Central Park Medical College from October 2020 and January 2021. To assess social avoidance and anxiety LIEBOWITZ Social Anxiety and avoidance Scale was employed. Paired sample t test and correlation was used to compare mean differences. A p value less than 0.05 were considered significant. Results: There was a reduction of score of social anxiety from covid wave 1 and wave 2 (26.73±4.65. 17.86±3.81) with p value of .001 and similarly there was a reduction of score of social avoidance (25.31±0.597 v/s 15.±0.3390) as well from wave 1 to wave 2 with p value of .001 Conclusion: There is a continuous decline in social avoidance and social anxiety which can cause an increase in covid 19 infection rate in order to combat that there’s need of prompt vaccination along with the precautionary measures to combat covid pandemic. MeSH Words: Covid-19, Social anxiety, social avoidance, covid wave.